Molecular composites of functional silica and natural rubber
By using the combination of double siliconxane hypolitics and natural rubber gel proof in tire manufacturing to form compositions with continuous molecular silicon dioxide networks, solve the problem of high rolling resistance in existing technologies, and achieve lower Rolling resistance and higher fuel economy.
Patent Information
- Application Number
- CN202011063627.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-01
- Filing Date
- 2020-09-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-09-30
AI Technical Summary
In the existing tire manufacturing, the weak interaction between natural rubber and carbon black filler leads to high rolling resistance, affecting fuel economy and sustainable development.
By mixing the water -soluble double -siliconane hypalide and a natural rubber gel proof, a composition containing continuous molecular silica networks is formed to improve the dispersion and adhesion of silicon dioxide in rubber.
Reduce the rolling resistance of the tire, improve the fuel economy, and reduce carbon dioxide emissions, and enhance the mileage of electric vehicles.
Smart Images

Figure CN112608531B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims the benefit of and priority to U.S. Provisional Patent Application No. 62 / 911,361, filed on October 6, 2019, entitled “Molecular Composites Comprising Functional Silica and Natural Rubber”; and U.S. Provisional Patent Application No. 63 / 033,204, filed on June 1, 2020, entitled “Molecular Composites Comprising Silica and Natural Rubber”, the disclosures of which are referenced herein. Technical Field
[0003] The invention relates to a rubber composite material and a method for making the same, in particular to a composition comprising natural rubber and an aminoalkyl silsesquioxane polymer and a method for making the composition. The composition is related to the tire manufacturing industry.
[0004] background
[0005] Tire manufacturers have been trying to create low rolling resistance (LLR) tires to meet the industry's sustainable development trend. "Rolling resistance" is generally defined as the energy lost to internal losses in the tire's composite microstructure for each rotation. A major source of internal losses is the weak interaction between the polymer and the typical carbon black filler material. The energy lost to tire rolling resistance is very significant. The U.S. Department of Energy (DOE) estimates that on average, 33% of the energy delivered to the wheel is lost due to rolling resistance. A comprehensive study by the National Highway Traffic Safety Association (NHTSA) shows that if rolling resistance is reduced by 30% without sacrificing wear resistance or traction, fuel economy can be improved by 3.3%. With an average annual consumption of 180 billion gallons of gasoline and diesel in the United States, tires with reduced rolling resistance can save 6 billion gallons of fuel each year. This is a measurable and important part of the nation's energy consumption. In addition, rolling resistance may be an even more important factor in electric vehicles because it can directly translate into longer driving range.
[0006] In the tire industry, "green tire" usually refers to an improved low rolling resistance tire made of materials from renewable resources. Low rolling resistance tires (LLR) first entered the market 25 years ago. Unfortunately, however, truly green tires have not yet been introduced.
[0007] In the manufacturing process of a typical LRR tread compound, amino- or hydroxy-functional solution-polymerized styrene-butadiene rubber (SSBR) is compounded with silica using specialty silanes such as bis(triethoxysilylpropyl) tetrasulfide (TESPT). During the initial stages of rubber compounding, the silane combines with silica to form tetrasulfide-functionalized silica. Then, during the rubber curing stage, the silica combines with the SSBR polymer (i.e., vulcanizes), creating covalent bonds between the SSBR polymer diene and the silica filler via the TESPT silane sulfur bridges. These covalent bonds are low-hysteresis materials in LRR compounds compared to the relatively weak polymer-filler interactions in conventional tire tread compounds using carbon black fillers. Hysteresis is typically measured by dynamic mechanical analysis (DMA) tan delta at 60°C. As an unwanted side effect, the silica-TESPT reaction can result in the generation of large amounts of dilute ethanol vapor during rubber compounding. This can have several negative consequences, including environmental hazards.
[0008] In the development of traditional tire rubber compounds, rolling resistance at 60°C (such as tanδ) is balanced with other tire properties such as traction, tread wear and fatigue resistance. Currently, all tire manufacturers use general-purpose natural rubber in large quantities because it is a low-cost renewable resource and has excellent physical properties when mixed with carbon black (CB) as a filler. However, NR-CB compounds have poor rolling resistance compared to modern compounds based on SSBR-TESPT silica. This is generally due to the weak interaction between the natural rubber polymer and the carbon black filler, which causes hysteresis energy losses with each rotation of the tire. Therefore, although NR-CB compounds are based on a renewable resource, they are not truly durable materials due to the relatively poor rolling resistance and energy losses during use. Rolling resistance is the main factor that determines the durability of tire rubber compounds, and the secondary factor is the materials used and durability of the tire.
[0009] Natural rubber-silica systems and other functional natural rubber systems have been extensively studied, but the high viscosity and poor compatibility of the non-polar, high molecular weight polyisoprene and highly polar silica make it difficult to properly disperse silica in these systems. In addition, these systems use expensive experimental raw materials that are not commercially available in large quantities, and also have disadvantages such as long processing time, low process yield, and high disposal costs for the generated byproduct waste.
[0010] The modern tire is a complex engineered composite structure consisting of a variety of rubber compounds, steel wires and textile reinforcements. Each compound is formulated to meet the requirements of a specific application, such as the tire's tread, sidewall, cleat, cord layer, bead, toe guard, top or carcass ply. Of these compounds, the tread is by far the most important for two reasons. First, the tread compound accounts for the largest proportion of the entire tire compound. Second, and most importantly, the tread is the most demanding application because it is the direct contact surface with the road and must simultaneously provide the best combination of high traction, high wear resistance and low rolling resistance. Currently, this combination of properties can be best achieved using silanes with SSBR polymers. The polymers currently used in tire treads are either high performance or renewable, but not both.
[0011]
[0006] Therefore, there is a long felt, yet unaddressed need for a composition comprising silica effectively dispersed and bonded in a natural rubber matrix, and a method for producing such a composition which is low cost and renewable. Brief description of the invention
[0012] Various aspects of the invention are briefly described herein according to one embodiment, and the invention generally relates to natural rubber and functional silica compositions for making tires and methods for producing the same. In at least one embodiment, the disclosed composition is a composition of a renewable elastomeric polymer for rubber compounding applications, such as low rolling resistance tire treads and winter tire tread applications. Since the composition of the present invention is more energy-efficient than current tire material compositions, the composition can also reduce fuel consumption, thereby reducing carbon dioxide emissions from fuel-powered vehicles and increasing the driving range of electric vehicles.
[0013] In various embodiments, the disclosed compositions can be prepared by mixing a water-soluble silsesquioxane oligomer into a natural rubber (NR) latex system, followed by in-situ formation of a continuous molecular silica network within the resulting polymer. In one embodiment, the resulting composition is a polymer that can be compounded into a low rolling resistance tread rubber using standard rubber compounding processes.
[0014] In one or more embodiments, the silsesquioxane oligomer solution used to form the disclosed composition has a low molecular weight and may contain three to seven silicon atoms. In many embodiments, the silsesquioxane oligomer may have high water solubility due to the silanol functional groups and amphoteric properties of the silsesquioxane oligomer. In at least one embodiment, the silsesquioxane oligomer and natural latex may form a molecular composition with less than 12 nanometers of silica domains. In one embodiment, the silsesquioxane oligomer may be an aminoalkyl silsesquioxane.
[0015] In one embodiment, a natural rubber composition including natural rubber and an aminoalkyl silsesquioxane polymer is disclosed.
[0016] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane polymer is generated by a chemical reaction of an aminoalkyl silsesquioxane oligomer having three, four, five, six or seven silicon atoms.
[0017] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer comprises an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer.
[0018] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer comprises aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer.
[0019] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0020] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 330 to about 552.
[0021] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer comprises aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0022] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer comprises 3 to 5 aminopropyl groups and 1 to 2 methylpropyl groups.
[0023] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0024] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer comprises an aminoalkyl silsesquioxane homopolymer oligomer.
[0025] In a further embodiment, the natural rubber composition, wherein the alkyl group of the aminoalkyl silsesquioxane homopolymer oligomer contains one, two, three, four, five or six carbon atoms.
[0026] In one embodiment, a method for forming a natural rubber composition is disclosed, comprising the steps of mixing natural rubber latex with a silsesquioxane oligomer solution; and drying the resulting mixture.
[0027] In further embodiments, the drying process includes adding the mixture to a substrate (e.g., a tray, sheet, or strip), partially drying the mixture to form a solid, removing the partially dried mixture from the substrate, and completing the drying process on an open rack or other device such that all sides of the partially dried mixture are exposed to the drying environment.
[0028] In a further embodiment, the drying process is a continuous drying process.
[0029] In further embodiments, the silsesquioxane oligomer in the method is water soluble.
[0030] In a further embodiment, the method further comprises the step of mixing a stabilizer with the silsesquioxane oligomer solution before mixing the silsesquioxane oligomer solution with the natural rubber latex.
[0031] In a further embodiment, the stabilizer in the method is selected from the group consisting of glucose delta-lactone, gluconic acid, ethylene glycol, an acid and a surfactant.
[0032] In a further embodiment, the method further comprises the step of adding precipitated silica to the obtained mixture before drying the obtained mixture.
[0033] In a further embodiment, the method wherein the silsesquioxane oligomer is an aminoalkyl silsesquioxane oligomer.
[0034] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is selected from the group consisting of aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer and aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0035] In one embodiment, a rubber processing additive is disclosed, comprising an aqueous solution of an aminoalkyl silsesquioxane oligomer and a stabilizer.
[0036] In a further embodiment, the stabilizer in the rubber processing additive is selected from the group consisting of ethylene glycol, glucose delta-lactone, gluconic acid, acids and surfactants.
[0037] In one embodiment, a natural rubber composition comprising natural rubber and an aminoalkyl silsesquioxane polymer is disclosed.
[0038] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane polymer is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 to 7 silicon atoms.
[0039] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane polymer is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 to 5 silicon atoms.
[0040] In a further embodiment, the natural rubber composition wherein the aminoalkyl silsesquioxane polymer is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 silicon atoms.
[0041] In a further embodiment, the natural rubber composition wherein the aminoalkyl silsesquioxane polymer is a reaction product of an aminoalkyl silsesquioxane oligomer having 4 silicon atoms.
[0042] In a further embodiment, in the natural rubber composition, the aminoalkyl silsesquioxane oligomer is an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0043] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups and 1 or 2 methylpropyl groups.
[0044] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups and 1 methylpropyl group.
[0045] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has 4 aminopropyl groups and 1 methylpropyl group.
[0046] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has 3 aminopropyl groups and 1 methylpropyl group.
[0047] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer is an aminoalkyl silsesquioxane homopolymer oligomer.
[0048] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane homopolymer has an alkyl group containing 1 to 6 carbon atoms.
[0049] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane homopolymer has an alkyl group containing 2 to 4 carbon atoms.
[0050] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane homopolymer has an alkyl group containing 3 carbon atoms.
[0051] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer is an aminopropyl silsesquioxane vinyl silsesquioxane copolymer oligomer.
[0052] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0053] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0054] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0055] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0056] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0057] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0058] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0059] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0060] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0061] In a further embodiment, the natural rubber composition, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0062] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight of less than about 850.
[0063] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 250 to about 600.
[0064] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 300 to about 550.
[0065] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 350 to about 500.
[0066] In a further embodiment, in the natural rubber composition, the aminoalkyl silsesquioxane oligomer is an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer.
[0067] In a further embodiment, the natural rubber composition, wherein the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer has repeating units of aminoalkylsilsesquioxane having an alkyl group having 1 to 6 carbon atoms, and repeating units of alkylsilsesquioxane having an alkyl group having 1 to 6 carbon atoms.
[0068] In a further embodiment, the natural rubber composition, wherein the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer has repeating units of aminoalkylsilsesquioxane having an alkyl group having 2 to 6 carbon atoms, and repeating units of alkylsilsesquioxane having an alkyl group having 1 to 4 carbon atoms.
[0069] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer has repeating units of aminoalkyl silsesquioxane having an alkyl group having 3 to 4 carbon atoms, and repeating units of alkyl silsesquioxane having an alkyl group having 1 to 3 carbon atoms.
[0070] In another aspect, a non-productive rubber formulation is disclosed, comprising a natural rubber composition as described elsewhere herein and a reinforcing silica filler.
[0071] In further embodiments, the composition further comprises a non-productive rubber formulation of carbon black.
[0072] In other embodiments, the composition further comprises a non-productive rubber formulation of additional natural rubber and / or one or more synthetic rubbers.
[0073] In a further embodiment, the synthetic rubber in the non-productive rubber formulation is selected from the group consisting of high cis-1,4-polybutadiene rubber, medium vinyl polybutadiene rubber, high vinyl polybutadiene rubber, synthetic polyisoprene rubber, isoprene-butadiene rubber, solution-polymerized styrene-butadiene rubber, emulsion-polymerized styrene-butadiene rubber, styrene-isoprene rubber, and styrene-isoprene-butadiene rubber.
[0074] In a further embodiment, a non-productive rubber formulation, wherein the composition further comprises at least one antidegradant.
[0075] In further embodiments, the non-productive rubber formulation has reinforcing silica present at a level ranging from 5 phr to 150 phr.
[0076] In further embodiments, the non-productive rubber formulation has reinforcing silica present at a level ranging from 10 phr to 120 phr.
[0077] In further embodiments, the non-productive rubber formulation has reinforcing silica present at a level ranging from 20 phr to 100 phr.
[0078] In further embodiments, the carbon black is present in the non-productive rubber formulation at a level ranging from 5 phr to 100 phr.
[0079] In further embodiments, the carbon black is present in the non-productive rubber formulation at a level ranging from 10 phr to 70 phr.
[0080] In another aspect, a productive rubber formulation is disclosed that includes a non-productive rubber formulation as described elsewhere herein and at least one rubber curing agent.
[0081] In a further embodiment, the rubber curing agent present in the productive rubber formulation is a sulfur curing agent.
[0082] In further embodiments, the composition further comprises a productive rubber formulation of at least one vulcanization accelerator.
[0083] In another aspect, a rubber article is disclosed, comprising a vulcanized rubber of a natural rubber formulation as described elsewhere herein.
[0084] In a further embodiment, the rubber product is a tire.
[0085] In a further embodiment, the rubber article is a conveyor belt.
[0086] In a further embodiment, the rubber product is a power transmission belt.
[0087] In one embodiment, a method for making a natural rubber composition is disclosed, comprising: (1) mixing an aqueous solution of an aminoalkyl silsesquioxane oligomer having 3 to 7 silicon atoms with natural rubber latex; (2) coagulating the natural rubber latex while reacting the aminoalkyl silsesquioxane oligomer in the latex to recover a uniform mixture of the aminoalkyl silsesquioxane oligomer and the natural rubber; and (3) removing residual water from the mixture of the aminoalkyl silsesquioxane oligomer and the natural rubber.
[0088] In a further embodiment, in step (1), a stabilizer is added to the latex before the aqueous solution of aminoalkyl silsesquioxane oligomer is added.
[0089] In a further embodiment, the method uses glucono delta-lactone as a stabilizer.
[0090] In a further embodiment, the method uses gluconic acid as a stabilizer.
[0091] In a further embodiment, the coagulation required in step (2) is a method in which coagulation is induced by adding an acid to the latex.
[0092] In a further embodiment, the method comprises lowering the pH of the latex to below about 7 by adding sufficient acid.
[0093] In a further embodiment, the method comprises adding sufficient acid to reduce the pH of the latex to a range of 6 to 6.5.
[0094] In a further embodiment, in step (1), water is additionally added to the latex before adding the aqueous solution of aminoalkyl silsesquioxane oligomer.
[0095] In further embodiments, the aminoalkyl silsesquioxane oligomer has 3 to 7 silicon atoms.
[0096] In further embodiments, the aminoalkyl silsesquioxane oligomer has 3 to 5 silicon atoms.
[0097] In a further embodiment, the aminoalkyl silsesquioxane oligomer has 3 silicon atoms.
[0098] In a further embodiment, the aminoalkyl silsesquioxane oligomer has 4 silicon atoms.
[0099] In a further embodiment, the aminoalkyl silsesquioxane oligomer is an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0100] In a further embodiment is a method wherein the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups and 1 or 2 methylpropyl groups.
[0101] In a further embodiment, the method wherein the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups and 1 methylpropyl group.
[0102] In a further embodiment is a method wherein the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 4 aminopropyl groups and 1 methylpropyl group.
[0103] In a further embodiment, the method wherein the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 3 aminopropyl groups and 1 methylpropyl group.
[0104] In a further embodiment, the aminoalkyl silsesquioxane oligomer is an aminoalkyl silsesquioxane homopolymer oligomer.
[0105] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer has an alkyl group containing 1 to 6 carbon atoms.
[0106] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer has an alkyl group containing 2 to 4 carbon atoms.
[0107] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer has an alkyl group containing 3 carbon atoms.
[0108] In a further embodiment, the aminoalkyl silsesquioxane oligomer is an aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer.
[0109] In a further embodiment, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0110] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0111] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0112] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0113] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0114] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0115] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0116] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0117] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0118] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0119] In further embodiments, the aminoalkyl silsesquioxane oligomer of the method has an average molecular weight of less than about 850.
[0120] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 250 to about 600.
[0121] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 300 to about 550.
[0122] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 350 to about 500.
[0123] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method is an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer.
[0124] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane with alkyl groups of 1 to 6 carbon atoms and repeating units of alkylsilsesquioxane with alkyl groups of 1 to 6 carbon atoms.
[0125] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane with alkyl groups of 2 to 6 carbon atoms and repeating units of alkylsilsesquioxane with alkyl groups of 1 to 4 carbon atoms.
[0126] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane with alkyl groups of 3 or 4 carbon atoms and repeating units of alkylsilsesquioxane with alkyl groups of 1 to 3 carbon atoms.
[0127] In one embodiment, a material composition is disclosed, including natural rubber and a siliceous material derived from a water-soluble silsesquioxane oligomer solution, wherein the silsesquioxane further includes a silanol.
[0128] In a further embodiment, the silsesquioxane oligomer in the material composition includes one or more of the following groups: methyl, vinyl, amino, glycidol, thiol, disulfide, polysulfide, epoxy compound, hydroxyl, etc.
[0129] In a further embodiment, the silsesquioxane oligomer in the material composition includes 2 to 7 silicon atoms.
[0130] In a further embodiment, the silsesquioxane oligomer in the material composition has an average molecular weight less than 500.
[0131] In a further embodiment, the material composition further comprises a stabilizer.
[0132] In a further embodiment, the stabilizer in the material composition is selected from the group consisting of glucono delta-lactone, gluconic acid, and a surfactant.
[0133] In a further embodiment, the material composition further comprises a cross-linking agent.
[0134] In further embodiments, the crosslinking agent is a material composition that reacts with one or more of the following groups: methyl, vinyl, diene, amino, glycidol, thiol, disulfide, polysulfide, epoxy, amine, and hydroxyl.
[0135] In further embodiments, the crosslinking agent comprises a reactive group selected from the group consisting of thiol, disulfide, polysulfide, aldehyde, dialdehyde, isocyanate, diisocyanate, diol, hydroxyl, ester, vinyl and cresol.
[0136] In a further embodiment, the cross-linking agent is selected from or derived from the group consisting of formaldehyde, acetaldehyde, glutaraldehyde, glyoxal, succinaldehyde, polyethylene glycol, diols, and polyols.
[0137] In a further embodiment, the color of the material composition is red.
[0138] In another aspect, disclosed is a method of preparing a material composition as described elsewhere herein, comprising the steps of mixing natural latex with a silsesquioxane oligomer and drying the resulting mixture.
[0139] In a further embodiment, the silsesquioxane oligomer is soluble in water.
[0140] In other embodiments, the water solubility of the silsesquioxane oligomer is greater than 5%, 10%, 15% or 20%.
[0141] In a further embodiment, a stabilizer is mixed with the oligomer prior to mixing with the latex, wherein the stabilizer is selected from the group consisting of glucono delta-lactone, gluconic acid, an acid, and a surfactant.
[0142] In a further embodiment, the method further comprises a degassing agent.
[0143] In a further embodiment, the method of concentrating or diluting latex is described.
[0144] In a further embodiment, the method of stabilizing latex is described.
[0145] In a further embodiment, the method of stabilizing the latex prior to adding the silsesquioxane is described.
[0146] In other embodiments, the method of stabilizing latex using ammonia is described.
[0147] In a further embodiment, the method further comprises adding precipitated silica to the aqueous mixture.
[0148] In one embodiment, a vulcanized rubber composition is disclosed, comprising at least 1%, 10%, 20%, 30% or 40% natural rubber, a minimum ash content of 10%, 15% or 20%, and any of the following properties: improved rolling resistance and durability; improved rolling resistance and wear resistance; tan-δ at 60°C is less than 0.15 or 0.10, and E' at -20°C is less than 20, 18, 16, 14, 12 or 10 MPa; E' at -20°C is less than 20, 18, 16, 14, 12 or 10 MPa, and tensile M300 is greater than 8, 10, 12, 14 or 16 MPa; E' at -20°C is less than 20, 18, 16, 14, 12 or 10 MPa, tensile M300 is greater than 8, 10, 12, 14 or 16 MPa, and tan-δ at 60°C is less than 0.15 or 0.10.
[0149] In further embodiments, the vulcanized rubber composition further comprises a material composition or a method described elsewhere herein.
[0150] In another aspect, a vulcanized rubber composition for a tire tread comprising a natural rubber composition as described elsewhere herein is disclosed, characterized by a magic triangle performance zone of increased rolling resistance, wear resistance, and wet traction.
[0151] In further embodiments, the tire tread cured rubber composition comprises a cured rubber composition described elsewhere herein.
[0152] In another aspect, disclosed is a tire comprising a vulcanized rubber composition as described elsewhere herein and / or a tire tread vulcanized rubber composition as described elsewhere herein.
[0153] In another aspect, the material composition, vulcanized rubber composition, tire tread vulcanized rubber composition, tire and / or method for making the material composition, as described elsewhere herein, wherein the natural rubber latex is replaced by an SBR emulsion.
[0154] In one embodiment, a natural rubber polyisoprene is disclosed, wherein the natural rubber polyisoprene is covalently bonded to an aminopropyl group of a silsesquioxane oligomer.
[0155] In further embodiments, the natural rubber polyisoprene further comprises a material composition, a vulcanized rubber composition, a tire tread vulcanized rubber composition, a tire, and / or a method of making the material composition.
[0156] In one embodiment, a vulcanized rubber composition is disclosed that includes rubber, silica, and an amino-functional silsesquioxane oligomer characterized by improved rolling resistance compared to similar compositions.
[0157] In further embodiments, the vulcanized rubber composition is further characterized by having a TGA derivative peak in the range of 200°C to 300°C.
[0158] In a further embodiment, the tire tread cured rubber composition is further characterized by having a TGA derivative shoulder between 500°C and 600°C.
[0159] In a further embodiment, the tire tread cured rubber composition is further characterized by having a TGA derivative peak between 200°C and 300°C and a TGA derivative shoulder between 500°C and 600°C.
[0160] In further embodiments, as described elsewhere herein, material compositions, vulcanized rubber compositions, tire tread vulcanized rubber compositions, tires, and / or methods of making material compositions, wherein the natural rubber latex is replaced by an SBR emulsion or the natural rubber polyisoprene is replaced by an SBR styrene-butadiene rubber polymer.
[0161] In another aspect, disclosed is a material composition as described elsewhere herein, further characterized by having silicon dioxide particles less than 100 nm, 50 nm, 20 nm, or 10 nm.
[0162] In further embodiments, the material composition is further characterized in that it is free of tetraalkoxysilanes or polyhedral oligomeric silsesquioxanes.
[0163] In another aspect, a tire is disclosed, including a tire containing the material composition, a vulcanized rubber composition, a tread vulcanized rubber composition, a tire, and / or a method of making the material composition as described elsewhere herein.
[0164] In a further embodiment, the material composition is further characterized by having a Shore A hardness greater than 51.
[0165] In a further embodiment, the material composition is further characterized in that it has a Shore A hardness greater than 55.
[0166] In a further embodiment, the material composition is further characterized by having a Shore A hardness greater than 59.
[0167] In one embodiment, a vulcanized rubber composition including natural rubber and an aminoalkyl silsesquioxane polymer is disclosed, wherein the vulcanized rubber composition has a TGA derivative peak in the range of 200°C to 300°C.
[0168] In a further embodiment, the vulcanized rubber composition is further characterized in that it has a TGA derivative shoulder in the range of 500°C to 600°C.
[0169] In a further embodiment, the method as described elsewhere herein further comprises step (4) of allowing the aminoalkyl silsesquioxane oligomer to polymerize in the natural rubber to form a mixture of aminoalkyl silsesquioxane polymers.
[0170] In one embodiment, a rubber processing additive is disclosed, comprising an aqueous solution of aminoalkyl silsesquioxane oligomer and glucono delta-lactone.
[0171] In one embodiment, a rubber processing additive is disclosed, comprising an aqueous solution of an aminoalkyl silsesquioxane oligomer and gluconic acid.
[0172] In one embodiment, a method for making a natural rubber composition is disclosed, comprising: (1) mixing a rubber processing additive as described elsewhere herein into natural rubber latex; (2) coagulating the natural rubber latex while reacting aminoalkyl silsesquioxane oligomers in the latex to recover a homogeneous mixture of aminoalkyl silsesquioxane oligomers and natural rubber; and (3) removing residual water from the mixture of aminoalkyl silsesquioxane oligomers and natural rubber.
[0173] In a further embodiment, the stabilizer is added to the latex before the aqueous solution of aminoalkyl silsesquioxane oligomer is added in step (1).
[0174] In a further embodiment, the stabilizer in the method is glucono delta-lactone.
[0175] In a further embodiment, the stabilizer in the method is gluconic acid.
[0176] In a further embodiment, in step (2), an acid is added to the latex to initiate coagulation.
[0177] In further embodiments, the method comprises adding sufficient acid to reduce the pH of the latex to below about 7.
[0178] In a further embodiment, the method comprises adding sufficient acid to reduce the pH of the latex to a range of 6 to 6.5.
[0179] In a further embodiment, in step (1), additional water is added to the latex before adding the aqueous solution of aminoalkyl silsesquioxane oligomer.
[0180] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has 3 to 7 silicon atoms.
[0181] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has 3 to 5 silicon atoms.
[0182] In a further embodiment, the aminoalkyl silsesquioxane oligomer has 3 silicon atoms.
[0183] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method has 4 silicon atoms.
[0184] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0185] In further embodiments, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 to 5 aminopropyl groups and 1 or 2 methylpropyl groups.
[0186] In further embodiments, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 to 5 aminopropyl groups and 1 methylpropyl group.
[0187] In a further embodiment, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 4 aminopropyl groups and 1 methylpropyl group.
[0188] In a further embodiment, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 aminopropyl groups and 1 methylpropyl group.
[0189] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminoalkyl silsesquioxane homopolymer oligomer.
[0190] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group containing 1 to 6 carbon atoms.
[0191] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group containing 2 to 4 carbon atoms.
[0192] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group containing 3 carbon atoms.
[0193] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer.
[0194] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0195] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0196] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0197] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0198] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0199] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0200] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0201] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0202] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0203] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0204] In further embodiments, the aminoalkyl silsesquioxane oligomer of the method has an average molecular weight of less than about 850.
[0205] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 250 to about 600.
[0206] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 300 to about 550.
[0207] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 350 to about 500.
[0208] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method is an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer.
[0209] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane having an alkyl group with 1 to 6 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 6 carbon atoms.
[0210] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane having an alkyl group with 2 to 6 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 4 carbon atoms.
[0211] In further embodiments, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method has repeating units of aminoalkylsilsesquioxane having an alkyl group with 3 to 4 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 3 carbon atoms.
[0212] In a further embodiment, the method further comprises: step (4) allowing the aminoalkyl silsesquioxane oligomer to polymerize to form a mixture of aminoalkyl silsesquioxane polymer in natural rubber.
[0213] In a further embodiment, in step (1), a stabilizer is added to the latex before the aqueous solution of aminoalkyl silsesquioxane oligomer is added.
[0214] In a further embodiment, the stabilizer in the method is glucono delta-lactone.
[0215] In a further embodiment, the stabilizer in the method is gluconic acid.
[0216] In a further embodiment, the coagulation process required in step (2) is induced by adding an acid to the latex.
[0217] In a further embodiment, the method comprises reducing the pH of the latex to below about 7 by adding a sufficient amount of acid.
[0218] In a further embodiment, the method comprises lowering the pH of the latex to a range of 6 to 6.5 by adding sufficient acid.
[0219] In a further embodiment, in step (1), additional water is added to the latex before the aqueous solution of aminoalkyl silsesquioxane oligomer is added.
[0220] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has 3 to 7 silicon atoms.
[0221] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has 3 to 5 silicon atoms.
[0222] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method has 3 silicon atoms.
[0223] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method has 4 silicon atoms.
[0224] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
[0225] In further embodiments, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 to 5 aminopropyl groups and 1 or 2 methylpropyl groups.
[0226] In a further embodiment, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 to 5 aminopropyl groups and 1 methylpropyl group.
[0227] In a further embodiment, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 4 aminopropyl groups and 1 methylpropyl group.
[0228] In a further embodiment, the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer in the method has 3 aminopropyl groups and 1 methylpropyl group.
[0229] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminoalkyl silsesquioxane homopolymer oligomer.
[0230] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group having 1 to 6 carbon atoms.
[0231] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group having 2 to 4 carbon atoms.
[0232] In further embodiments, the aminoalkylsilsesquioxane homopolymer oligomer in the method has an alkyl group containing 3 carbon atoms.
[0233] In a further embodiment, the aminoalkyl silsesquioxane oligomer in the method is an aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer.
[0234] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0235] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0236] In a further embodiment, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0237] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0238] In a further embodiment, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0239] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0240] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0241] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0242] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0243] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer in the method has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0244] In further embodiments, the aminoalkyl silsesquioxane oligomer of the method has an average molecular weight of less than about 850.
[0245] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 250 to about 600.
[0246] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 300 to about 550.
[0247] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method has an average molecular weight in the range of about 350 to about 500.
[0248] In further embodiments, the aminoalkyl silsesquioxane oligomer in the method is an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer.
[0249] In a further embodiment, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method contains repeating units of aminoalkylsilsesquioxane having an alkyl group with 1 to 6 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 6 carbon atoms.
[0250] In a further embodiment, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method contains repeating units of aminoalkylsilsesquioxane having an alkyl group with 2 to 6 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 4 carbon atoms.
[0251] In a further embodiment, the aminoalkylsilsesquioxane-alkylsilsesquioxane copolymer oligomer in the method contains repeating units of aminoalkylsilsesquioxane having an alkyl group with 3 or 4 carbon atoms and repeating units of alkylsilsesquioxane having an alkyl group with 1 to 3 carbon atoms.
[0252] In one embodiment, a natural rubber composition is disclosed that includes natural rubber and an aminoalkyl silsesquioxane polymer, the aminoalkyl silsesquioxane polymer including a silanol.
[0253] In a further embodiment, the aminoalkyl silsesquioxane polymer natural rubber composition is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 to 7 silicon atoms and an aminoalkyl silsesquioxane polymer including silanol.
[0254] In a further embodiment, the aminoalkyl silsesquioxane polymer natural rubber composition is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 to 5 silicon atoms and an aminoalkyl silsesquioxane polymer including silanol.
[0255] In a further embodiment, the aminoalkyl silsesquioxane polymer natural rubber composition is a reaction product of an aminoalkyl silsesquioxane oligomer having 3 silicon atoms and an aminoalkyl silsesquioxane polymer including silanol.
[0256] In a further embodiment, the aminoalkyl silsesquioxane polymer natural rubber composition is a reaction product of an aminoalkyl silsesquioxane oligomer having 4 silicon atoms and an aminoalkyl silsesquioxane polymer including silanol.
[0257] In a further embodiment, the natural rubber composition of the aminoalkyl silsesquioxane oligomer is an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer including silanol.
[0258] In further embodiments, the natural rubber composition of the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups and 1 or 2 methylpropyl groups including silanol.
[0259] In a further embodiment, the natural rubber composition of the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 3 to 5 aminopropyl groups including silanol and 1 methylpropyl group.
[0260] In a further embodiment, the natural rubber composition of the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has 4 aminopropyl groups including silanol and 1 methylpropyl group.
[0261] In a further embodiment, the natural rubber composition of the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer has three aminopropyl groups and one methylpropyl group including silanol.
[0262] In a further embodiment, the natural rubber composition of the aminoalkyl silsesquioxane oligomer is an aminoalkyl silsesquioxane homopolymer oligomer including silanol.
[0263] In a further embodiment, the aminoalkylsilsesquioxane homopolymer oligomer is a natural rubber composition having an alkyl group containing 1 to 6 carbon atoms and a silanol.
[0264] In a further embodiment, the aminoalkylsilsesquioxane homopolymer oligomer is a natural rubber composition having an alkyl group containing 2 to 4 carbon atoms and a silanol.
[0265] In a further embodiment, the aminoalkyl silsesquioxane homopolymer is a natural rubber composition having an alkyl group containing 3 carbon atoms and a silanol.
[0266] In a further embodiment, the aminoalkyl silsesquioxane oligomer is a natural rubber composition of aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer including silanols.
[0267] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units of the silanol-containing natural rubber composition in a range of 3:2 to 6:1.
[0268] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0269] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0270] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0271] In further embodiments, the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0272] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 3:2 to 6:1.
[0273] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 5:1.
[0274] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 4:1.
[0275] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 2:1 to 3:1.
[0276] In further embodiments, the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer containing silanols has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in a range of 9:4 to 11:4.
[0277] In a further embodiment, the aminoalkyl silsesquioxane oligomer of the natural rubber composition has an average molecular weight of less than about 850, the oligomer further comprising a silanol.
[0278] In further embodiments, the natural rubber composition of the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 250 to about 600, the oligomer further comprising a silanol.
[0279] In further embodiments, the natural rubber composition of the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 300 to about 550, the oligomer further comprising a silanol.
[0280] In further embodiments, the natural rubber composition of the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of about 350 to about 500, the oligomer further comprising a silanol.
[0281] In a further embodiment, the aminoalkyl silsesquioxane oligomer is a natural rubber composition of aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer, and the oligomer further comprises a silanol.
[0282] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer has repeating units of aminoalkyl silsesquioxane having an alkyl group with 1 to 6 carbon atoms and repeating units of alkyl silsesquioxane having an alkyl group with 1 to 6 carbon atoms, the oligomer further comprises silanol.
[0283] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer has aminoalkyl silsesquioxane repeating units in which the alkyl group has 2 to 6 carbon atoms and alkyl silsesquioxane repeating units in which the alkyl group has 1 to 4 carbon atoms, the oligomer further comprises silanol.
[0284] In a further embodiment, the natural rubber composition, wherein the aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer has aminoalkyl silsesquioxane repeating units in which the alkyl group has 3 to 4 carbon atoms and alkyl silsesquioxane repeating units in which the alkyl group has 1 to 3 carbon atoms, the oligomer further comprises silanol.
[0285] In another aspect, a non-productive rubber formulation is disclosed that includes a natural rubber composition as described elsewhere herein and a reinforcing silica filler.
[0286] In a further embodiment, the natural rubber composition comprises a non-productive rubber formulation of carbon black.
[0287] In further embodiments, the natural rubber composition comprises a non-productive rubber formulation of additional natural rubber and / or one or more synthetic rubbers.
[0288] In further embodiments, the one or more non-productive rubber formulations of synthetic rubbers are selected from high cis-1,4-polybutadiene rubber, medium vinyl polybutadiene rubber, high vinyl polybutadiene rubber, synthetic polyisoprene rubber, isoprene-butadiene rubber, dissolved styrene butadiene rubber, latex styrene butadiene rubber, styrene-isoprene rubber, and styrene-isoprene-butadiene rubber.
[0289] In a further embodiment, the non-productive rubber formulation of the natural rubber composition includes at least one antidegradant.
[0290] In a further embodiment, the reinforcing silica filler level of the non-productive rubber formulation is in the range of 5 phr to 150 phr.
[0291] In a further embodiment, the reinforcing silica filler level of the non-productive rubber formulation is in the range of 10 phr to 120 phr.
[0292] In a further embodiment, the reinforcing silica filler level of the non-productive rubber formulation is in the range of 20 phr to 100 phr.
[0293] In further embodiments, the non-productive rubber formulation has a carbon black level in the range of 5 phr to 100 phr.
[0294] In further embodiments, the non-productive rubber formulation has a carbon black level in the range of 10 phr to 70 phr.
[0295] In another aspect, a productive rubber formulation is disclosed that includes a non-productive rubber formulation as described elsewhere herein and at least one rubber curative.
[0296] In a further embodiment, the productive rubber formulation has at least one rubber curing agent as a sulfur curing agent.
[0297] In a further embodiment, the natural rubber composition in the productive rubber formulation includes at least one cure accelerator.
[0298] In another aspect, a rubber article comprising a vulcanized rubber is disclosed, wherein the vulcanized rubber comprises a natural rubber formulation as described elsewhere herein.
[0299] In a further embodiment, the rubber product is a tire.
[0300] In a further embodiment, the rubber article is a conveyor belt.
[0301] In a further embodiment, the rubber product is a power transmission belt.
[0302] Although changes and modifications may be made to the invention without departing from the spirit and scope of the invention, the factors, features and claims of the invention will become more apparent from the following detailed written description of the preferred embodiments and related aspects in conjunction with the accompanying drawings.
[0303] BRIEF DESCRIPTION OF THE DRAWINGS
[0304] The accompanying drawings illustrate one or more embodiments and / or aspects of the present invention and, in conjunction with the written description, explain the principles of the present invention. Wherever possible, the same reference numerals are used throughout the drawings to represent the same or similar elements in the embodiments, wherein:
[0305] Figure 1 An exemplary method of forming an exemplary composition according to one embodiment of the present invention is described.
[0306] Figure 2 is a DMA tan-delta plot of an exemplary composition compared to a control according to one embodiment of the present invention;
[0307] Figure 3 is a microentropy thermogravimetric analysis (TGA) graph of an example composition including GDL and a control not including GDL according to one embodiment of the present invention;
[0308] Figure 4A is a graph of tensile stress-strain curves of an exemplary composition according to one embodiment of the present invention compared to a control;
[0309] Figure 4B is a graph of tensile stress-strain curves of an exemplary composition according to one embodiment of the present invention compared to a control;
[0310] Figure 5 is a graph of a nanoDMA histogram of storage modulus of an exemplary composition according to an embodiment of the present invention compared to a control;
[0311] Figure 6 is a graph of DMA E' according to an exemplary composition of one embodiment of the present invention compared to a control;
[0312] Figure 7 is a graph of DMA E" curves of an exemplary composition according to one embodiment compared to a control. Detailed Description
[0313] In order to make the principle of the present invention easy to understand, the embodiments shown in the reference drawings and the specific descriptive language used are now explained. However, it should be understood that the scope of the present invention is not limited thereby; any technician in the industry may make changes or modifications to the described or illustrated embodiments and the inventive principles and related applications of the present invention shown therein. All scope limitations should be determined according to the provisions of the claims.
[0314] Whether or not a term is capitalized does not determine or limit the meaning of that term. Capitalized terms used in this document shall have the same meaning as non-capitalized terms, except where the context clearly indicates that the capitalized term has a restrictive meaning. However, capitalization or the lack of capitalization in the rest of this document shall not indicate any limiting meaning unless the context clearly indicates otherwise.
[0315] The present invention generally relates to rubber composite materials and methods for making the same, and more specifically to compositions comprising natural rubber and aminoalkyl silsesquioxane polymers and methods for making the same. In various embodiments, a chemical composition is produced by mixing a water-soluble silsesquioxane oligomer into a natural rubber (NR) latex system and then forming a continuous molecular silica network in situ within the polymer. The resulting composition can be compounded into a low rolling resistance tread rubber for manufacturing tires.
[0316] In various embodiments, a molecular composition (also referred to as a "composite") of functional silica in a natural rubber latex / polymer system using a stable, high concentration, low molecular weight silsesquioxane (SSQ) oligomer aqueous solution is disclosed. Generally speaking, the use of SSQ to enhance natural rubber is not understood by those skilled in the art of rubber composite technology, and the manufacturers of such compounds do not recommend the use of this method. In many embodiments, the composition can be made by liquid phase mixing. In many embodiments, the low molecular weight, high water solubility and amphiphilic solubilizing properties of silsesquioxane oligomers provide unique opportunities for interaction with natural rubber (isoprene) chain ends and phospholipid / protein layers on natural rubber latex particles. In one embodiment, the disclosed silica component in natural rubber can improve the performance and processing properties of low rolling resistance tread rubbers, and can enable the manufacture of a new generation of low-cost, more sustainable low rolling resistance tires.
[0317] In various embodiments, the siloxane used to form the inventive composition may have a concentration greater than or equal to 5.0%, which is generally much higher than silanes and typical uses of siloxanes in aqueous solutions due to solubility limitations (0.1-0.5%). In one or more embodiments, the siloxane used in the composition forming embodiments is amphoteric and stable. In at least one embodiment, the high siloxane concentration enables the resulting silica network to function as a structural enhancer rather than just an adhesion promoter or primer.
[0318] In various embodiments, low molecular weight silsesquioxane oligomers (3 to 7 silicon atoms) can be used to form the composition of the present invention. In at least one embodiment, the silsesquioxane oligomer used may have a backbone containing 3, 4, 5, 6 or 7 silicon atoms. In at least one embodiment, the molecular weight of the silsesquioxane oligomer having 3 to 7 silicon atoms in the backbone may be in the range of about 330 to 552. In many embodiments, the molecular weight of the silsesquioxane oligomer having 3 to 7 silicon atoms in the backbone may be as high as about 850. In one embodiment, the lower molecular weight provides better fluidity, dispersibility and latex polymer interaction between the silsesquioxane oligomer and natural latex, as opposed to the molecular weight of the silsesquioxane oligomer having 8 silicon atoms. In one or more embodiments, the higher molecular weight silsesquioxane oligomer may be insoluble at high concentrations and low viscosities, which will result in any resulting silica network being unable to function as a structural reinforcement for natural rubber.
[0319] In several embodiments, the addition of one or more stabilizers can stabilize the silsesquioxane oligomer solution and natural latex mixture. In one or more embodiments, the natural rubber particles can be stabilized by proteins and phospholipids (e.g., by adding one or more stabilizers). In one embodiment, the stabilizer can be glucono delta-lactone, ammonia, or similar chemicals. In at least one embodiment, the silsesquioxane oligomer solution may be incompatible with natural latex without a stabilizer because SSQ can destabilize the natural latex particles. In many embodiments, the SSQ / natural latex mixture may undergo a reaction process to distribute silicon through the resulting natural rubber polymer. In one embodiment, the reaction process can be a coagulation / condensation reaction. In at least one embodiment, the SSQ reacts to form a network structure throughout the natural rubber polymer. In one or more embodiments, previous methods using discrete silica particle dispersions were unable to form molecular-scale composites because the dispersed discrete silica particles were not small enough to form molecular-scale composites.
[0320] In various embodiments, a stabilizer (e.g., glucono-δ-lactone) and a coordinated coagulation / condensation reaction are added to gradually reduce the mixture from its initial pH value of 10.5 to a neutral pH value by adding a stabilizer. In at least one embodiment, in the coagulation / condensation reaction, natural latex coagulates to form a natural rubber gel, and silsesquioxane oligomers form silica after a condensation reaction. In many embodiments, the gradual reduction in pH achieved by the gradual acidification of the stabilizer enables the coagulation of natural latex to be controlled while the silsesquioxane oligomers condense into a reinforced silica network. In one or more embodiments, other stabilizers for dispersing and stabilizing the system may include, for example, ethylene glycol and surfactants, and other additives (e.g., acids with or without buffers) may be used to induce coagulation / precipitation reactions.
[0321] In several embodiments, the silsesquioxane oligomers are formed at high pH values from amino-functionalized silanes that form stable oligomers at high concentrations. In many embodiments, the silsesquioxane oligomers may include other functional groups in addition to the amino functional groups. In one or more embodiments, the silsesquioxane oligomers in aqueous solution may contain at least one silanol group (Si-OH). In at least one embodiment, the additional functional groups may include, but are not limited to, methyl, vinyl, mercapto, mercaptopropyl, glyaminopropyl, disulfide, and polysulfide functional silanes. In one embodiment, the silsesquioxane oligomers may be aminoalkyl silsesquioxane oligomers. In one or more embodiments, examples of aminoalkyl silsesquioxane oligomers may include, but are not limited to, aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomers or aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomers. In many embodiments, the silsesquioxane oligomers may be aminoalkyl silsesquioxane homopolymer oligomers. In many embodiments, the alkyl group in the aminoalkyl silsesquioxane oligomer can contain 1, 2, 3, 4, 5 or 6 carbon atoms. In one embodiment, the aminoalkyl silsesquioxane oligomer can have the following structure:
[0322]
[0323] wherein R is a functional group, n is at least 1, and the sum of m and n is less than or equal to 5.
[0324] In various embodiments, the aminoalkyl silsesquioxane oligomer may include one or more repeating units. In at least one embodiment, the repeating unit is a portion of an oligomer or polymer that is repeated to produce the oligomer or polymer. For example, in one embodiment, the aminoalkyl silsesquioxane oligomer may have two or three amino functional silanes and one additional silane in a ratio of two or three amino functional silanes to one additional silane (2:1 or 3:1).
[0325] In one or more embodiments, other elastic latexes can be used to replace natural latex. For example, in one embodiment, SBR emulsion can replace natural latex in whole or in part.
[0326] Please refer to the accompanying drawings to illustrate the basic process and structure of the system and method of the present invention. Figure 1 , which illustrates an exemplary method 100 for forming an exemplary composition according to one embodiment of the present invention. Figure 1 The exemplary method 100 shown in FIG. 1 is merely representative of one method or embodiment of the present invention and may also be applied in other aspects according to various embodiments of the present invention.
[0327] like Figure 1 , an exemplary method 100 for preparing an exemplary natural rubber composition is described. According to one embodiment, in step 102 in method 100, a silsesquioxane oligomer solution may be provided. In one or more embodiments, the silsesquioxane oligomer solution may be about a 20% silsesquioxane oligomer solution. In at least one embodiment, the silsesquioxane oligomer solution may be water-soluble and / or in an aqueous solution. In one embodiment, the silsesquioxane oligomer may be an aminoalkyl silsesquioxane oligomer, an aminoalkyl silsesquioxane-alkyl silsesquioxane co-oligomer, an aminoalkyl silsesquioxane homopolymer oligomer, or an aminoalkyl silsesquioxane-alkyl silsesquioxane co-oligomer. For example, in one embodiment, the silsesquioxane oligomer may be an aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer, an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer, or other similar compounds.
[0328] In various embodiments in step 104, a stabilizer may be provided and mixed with the silsesquioxane oligomer solution. In one embodiment, the stabilizer may be mixed with the natural latex (as described in step 106 below) rather than with the silsesquioxane oligomer solution. In many embodiments, the stabilizer may be glucono delta-lactone, gluconic acid, ethylene glycol, an acid or surfactant or other similar compound. In at least one embodiment, the stabilizer and the silsesquioxane oligomer solution may be mixed for a specific amount of time, such as approximately 600 seconds.
[0329] In several embodiments in step 106, natural latex and a deaerator may be provided and mixed together. In many embodiments, the natural latex may be about 62% natural latex. In one or more embodiments, the deaerator may be deaerator BYK-1740 or another similar compound. In at least one embodiment, the natural latex and the deaerator may be mixed for a specific amount of time, such as about 30 seconds. In one embodiment, the natural latex and the deaerator may be mixed by a low shear mixture. In another embodiment, after the natural latex is mixed with the deaerator, precipitated silica powder may be added and mixed into the resulting natural latex / deaerator mixture. In one embodiment, the precipitated silica powder may be Solvay Z1165MP or similar precipitated silica powder.
[0330] In various embodiments in step 108, the mixture generated in step 104 and the mixture generated in step 106 may be mixed together. In one or more embodiments, the mixture generated in step 104 and the mixture generated in step 106 may be mixed together by low shear mixing. In at least one embodiment, the mixture generated in step 104 and the mixture generated in step 106 may be mixed for a specific period of time, such as approximately 300 seconds.
[0331] In various embodiments in step 110, glutaraldehyde may be mixed into the mixture generated in step 108. In one embodiment, the glutaraldehyde may be 2% glutaraldehyde in an aqueous solution. In one or more embodiments, the glutaraldehyde may be mixed into the mixture generated in step 108 within a specific time period (e.g., 600 seconds). In at least one embodiment, the glutaraldehyde may be mixed with the mixture generated in step 108 via a low shear mixture. In alternative embodiments, the glutaraldehyde may not be mixed, and the process may skip step 110 and proceed directly from step 108 to step 112.
[0332] In various embodiments of step 112, the mixture produced in step 110 may be dried. In many embodiments, the mixture produced in step 110 may be dried within a specific period of time. In one or more embodiments, the mixture produced in step 110 may be dried at a specific temperature. For example, in one embodiment, the mixture produced in step 110 may be dried at 60° C. for approximately 48 hours.
[0333] In various embodiments, the resulting compound after drying in step 112 is an exemplary natural rubber / silsesquioxane polymer composition.
[0334] Go to Figure 2 , according to one embodiment of the present invention, a DMA tan-δ curve of an exemplary composition compared with a control. In various embodiments, Figure 2Dynamic Mechanical Analysis (DMA) tan-δ of the composition of the present invention (exemplary formulation tan-δ) is shown. In many embodiments, DMA tan-δ can measure the hysteresis of the composition of the present invention. In one or more embodiments, the composition of the present invention has a lower tan-δ than the control at a temperature above about -13°C. In one embodiment, the lower DMA measurement of the composition of the present invention can indicate improved bond formation between the natural latex and the silica in the silsesquioxane oligomer. In at least one embodiment, Figure 2 The comparative graph shown in is a natural latex that has not been mixed with silsesquioxane or glucono delta-lactone (Compound 1 listed in Example 3 below).
[0335] Go to Figure 3 According to one embodiment of the present invention, a TGA microentropy curve for an exemplary composition including GDL and a control not including GDL is shown here. In one or more embodiments, the derivative peak between 190-290°C indicates the presence of GDL. In several embodiments, Figure 3 The control had no GDL mixed into the silsesquioxane oligomer solution or the natural latex mixture (Sample 5 of Example 3, see below).
[0336] Go to Figure 4A , a tensile stress-strain graph of an exemplary composition according to one embodiment of the present invention compared to a control is shown here. In multiple embodiments, the composition of the present invention can have a strain percentage stress that is about 38% higher than the control. In one or more embodiments, the composition of the present invention can have a more linear stress-strain behavior, indicating that the bond formation between the natural latex and the silica from the silsesquioxane oligomer is improved. In at least one embodiment, Figure 2 The control graph shown in is a natural latex that was not mixed with silsesquioxane or glucono delta-lactone (Compound 1 in Example 3 below).
[0337] Go to Figure 4B , according to one embodiment of the present invention, a zoomed in area is shown here. Figure 4A Graphics.
[0338] Go to Figure 5, the storage modulus (E') nano DMA histograms of the control (compound 1 from Example 3, see below) and the exemplary composition (compound 3 from Example 3, see below) are compared. In one or more embodiments, the specifications of the nano DMA histogram are as follows: the equipment used is Bruker Nano-DMA, the measurement sample area is 5 microns x 5 microns, the conditions are T = 27 ° C and the frequency is 100 Hz, the nano DMA resolution is 100 nanometers, and the histogram has 512 bins with a range of 3.39 GPa.
[0339] In at least one embodiment, the image shows a unique bimodal E' histogram for the exemplary composition, with a first peak at approximately 0.01 GPa, a characteristic secondary peak at 0.04 GPa, and a width of 0.02 to 0.10 GPa.
[0340] Go to Figure 6 , an exemplary combined DMAE' curve graph of one embodiment of the present invention compared with a control is shown here. In at least one embodiment, Figure 2 The control graph shown in is a natural latex that was not mixed with silsesquioxane or glucono delta-lactone (Compound 1 in Example 3 below).
[0341] Go to Figure 7 , an exemplary combined DMAE" graph of one embodiment according to the present invention compared with a control is shown here. In at least one embodiment, Figure 2 The control graph shown in is a natural latex that was not mixed with silsesquioxane or glucono delta-lactone (Compound 1 in Example 3 below).
[0342] Example
[0343] The following examples illustrate certain embodiments of the present invention, and test results associated therewith. These examples are provided for illustrative purposes only and are not intended to limit the scope of the invention described in the present invention. Instead, these examples provide useful guidance for certain elements, ratios, and test results of various specific embodiments of the present invention.
[0344] Example 1
[0345] According to one embodiment, a stable natural latex / SSQ oligomer can be achieved, and the resulting composition can be practical. In various embodiments, the composition of the present invention can be prepared by the following steps: 1) adding distilled water to natural latex, 2) adding glucono-δ-lactone (GDL), 3) stirring for a period of time, 4) adding aminoalkyl silsesquioxane oligomer to the aqueous solution, 5) stirring for a period of time, 6) waiting for a period of time to acidify the resulting mixture to a desired pH value, and 7) dehydrating the mixture and pressing at a specific temperature.
[0346] For example, in one embodiment, a recipe may include:
[0347] 1. Provide about 40 grams of ammonia stabilizer, centrifuge and concentrate to 62% natural latex, pH 10.5.
[0348] 2. Add about 100g of distilled water.
[0349] 3. Add about 4 grams of glucono-delta-lactone (GDL).
[0350] 4. Stir the above solution using a low shear magnetic stir bar for about 30 seconds.
[0351] 5. Add about 10 grams of aminopropyl / methyl silsesquioxane oligomer to the aqueous solution at a concentration of 20% and a pH of 11.
[0352] 6. Stir the above solution for about 60 seconds.
[0353] 7. Wait about two hours for acidification to a pH of 6 to 6.5.
[0354] 8. The gel was removed from the slurry, squeezed to remove water, and dried at a temperature of about 70°C.
[0355] It was observed in the above experiments that GDL gradually hydrolyzed and acidified, thereby reducing the pH of the natural latex and inducing coagulation of the natural latex. In certain test protocols, the addition of GDL before the addition of the oligomer can temporarily improve the stability of the latex / oligomer and allow for a higher concentration of oligomers. In at least one embodiment, testing of the resulting composition included TGA (showing a silica content of approximately 5%) and DMA analysis showing a glass transition temperature (Tg) shift from -63°C to -60°C. In the above examples, Tg showed a significant enhancement effect at relatively low silica loadings and showed that the molecular composite material was effectively enhanced. The Tg shift is a positive indicator of the balance of wet traction-rolling resistance parameters necessary to improve the utilization of natural rubber in LRR tread rubbers. In at least one embodiment, SEM / EDX silica mapping showed that the silica was uniformly distributed throughout the sample with no signs of silica agglomeration.
[0356] Example 2
[0357] In several embodiments, a scaled-up process for forming the composition of the present invention is described, and the steps of the process are generally the same as those in the above examples. For example, in one embodiment, the formulation may include:
[0358] 1. Provides approximately 330.4 grams of 62% natural latex.
[0359] 2. Add approximately 800 grams of distilled water.
[0360] 3. Add about 32 grams of GDL.
[0361] 4. Stir the above solution using a low shear magnetic stir bar for about 30 seconds.
[0362] 5. Add about 85 grams of aminopropyl / methyl silsesquioxane oligomer.
[0363] 6. Stir the above solution with a magnetic bar for about 60 seconds.
[0364] 7. A solution of about 1285.4 grams was finally produced.
[0365] 8. Wait about 6 hours for it to acidify to a pH of about 5.0.
[0366] 9. The gel was removed from the slurry, squeezed to remove water, and dried at approximately 122°F for about 72 hours.
[0367] In the above example, the natural rubber latex may coagulate into a slurry and gel after 6 hours of acidification, with a final pH of 5.0. In at least one test case, 204 grams of loose slurry was dried to 37 grams of whey solids. In this example, the gel was wet pressed to 595 grams and dried at 122°F for 72 hours to 245 grams.
[0368] Example 3
[0369] In this example, a method of forming the composition of the present invention is described, but the addition of distilled water is excluded, which inhibits gel-serum separation and retains substantially all oligomers in the NR as confirmed by TGA. In this example, the latex-oligomer mixture was poured into a pan and dried without gel-serum separation. In the table below, AP-V is aminopropyl silsesquioxane-vinyl silsesquioxane (such as Gelest WSA-6501) and AP-M is aminopropyl silsesquioxane-methyl silsesquioxane (such as Gelest WSA-7011). For example, the table below shows the results for six samples.
[0370] In this example, the process of the sample is as follows: 1) add glucono-δ-lactone to approximately 20% of a silsesquioxane oligomer solution, 2) mix for a period of time, 3) add a deaerator (such as BYK-1740) to 62% of natural rubber latex, 4) low shear mix the natural latex and the deaerator for a period of time, 5) low shear mix the natural latex mixture in step 4 and the oligomer solution mixture in step 2 for a period of time, 6) add glutaraldehyde to the mixture generated in step 5, 7) low shear mix the glutaraldehyde and the natural rubber / oligomer mixture, and 8) dry the mixture generated in step 7 at a specific temperature for a period of time.
[0371] Table 1 below shows the results of the above-described formation process in this example.
[0372] 1 2 3 4 5 6 Silsesquioxane oligomer types n / a AP-V AP-V AP-M AP-M AP-V 20% oligomer solution, g 0 504 457 486 486 835 Glucono-δ-lactone, g 0 86 86 86 0 86 Premixed GDL and oligomers, s n / a 600 600 600 n / a 600 62% latex, g 1680 1440 1440 1440 1440 1440 Dry rubber content (DRC), g 1064 912 912 912 912 912 Degassing agent BYK-1740, g 0 10 0 10 10 10 Low shear mix 1740 with latex, s n / a 30 n / a 30 30 30 Low shear mixing of latex and oligomers, s 30 300 300 300 300 300 Glutaraldehyde 2%, g 0 144 0 137 137 234 Low shear mixing, 0 600 600 600 600 600 Drying temperature, °C 50 50 50 50 50 50 Drying time, h 48 48 48 48 48 48 Total solids 1064 1102 1003 1098 1012 1170 Oligomer, g 0 101 91 97 97 167 <![CDATA[SiO2 equivalent, g]]> 0 52 48 52 52 87 <![CDATA[SiO2 equivalent, %]]> 0.0% 5.0% 4.5% 5.0% 5.4% 8.0%
[0373] Table 1 – Results of the generation process
[0374] In this example, the resulting composition from Table 1 is further mixed to form a rubber compound. The first process of the resulting composition in Table 1 is as follows: 1) set the mixer to about 55 revolutions per minute (RPM), 2) add the resulting composition (polymer composition) to the mixer and crush for about 30 seconds while compacting, 3) lift and add the other ingredients of the first process, and then compact downward, 4) sweep at about 200°F and pour at about 300°F. In one or more embodiments, the terms "compact", "tamp", "sweep", and "pour" have standard meanings understood by ordinary technicians in the rubber manufacturing field.
[0375] In this example, the compound from the first pass was processed in the final pass of the second day. The steps for the final pass were as follows: 1) set the mixer to approximately 45 RPM, 2) add approximately half of the compound from the first pass to the mixer, 3) add the compound cure package listed in the final pass section of Table 2, 4) add the remaining compound from the first pass, 5) sweep at approximately 170°F and pour at approximately 200°F.
[0376] The compound formulations for these examples are shown in Table 2 below.
[0377]
[0378] Table 2 – Compound formulations
[0379] In this example, the compounds generated from the final process were tested and the test results are shown in Table 3.
[0380]
[0381]
[0382] Table 3 - Test results of compounds generated in the final process
[0383] Example 4
[0384] In Example 4, a formulation identical to Example 3 Composite Formulation 3 was prepared, except that after the silsesquioxane oligomer / GDL mixture was added to the natural latex, Solvay Z1165MP precipitated silica powder was added directly to the latex / silsesquioxane oligomer / GDL mixture after mixing for about 10 minutes. In this example, the mixture solidified immediately after the addition of the silica. The mixture was then transferred to a pan and dried at about 60°C for about 48 hours. In this example, the amount of silica added was approximately 20% of the total solids content of the entire batch.
[0385] After drying, three strips were cut from the dried mixture and stretched by approximately 300%. In this example, the strips broke after 3, 5, and 6 stretches. During the stretching process, loose silica was observed to fall off the strips. In this example, the silica weight loss was approximately equal to 5% of the total weight of the strip, which was equivalent to approximately 25% of the weight of silica added.
[0386] Example 5
[0387] In this Example 5, the same formulation as Example 3 Composite Formulation 3 was prepared, except that Solvay Z1165MP precipitated silica powder was added directly to the silsesquioxane oligomer / GDL mixture to form a paste after mixing for about 10 minutes before the silsesquioxane oligomer / GDL mixture was added to the latex. Distilled water was added to form a slurry, and the resulting slurry was mixed for about 5 minutes at 300 rpm using a Cowles-blade mixer. The slurry mixture was then added to the latex and mixed for about 15 minutes according to the method of Example 3 Composite Formulation 3. In this example, the mixture was poured into a pan and dried at about 60°C for about 48 hours. In this example, the amount of silica added was approximately equivalent to 20% of the total solid content of the entire batch.
[0388] After drying, three strips were cut from the dried mixture and stretched by about 300%. In this example, none of the strips broke after 50 stretches. During the stretching process, loose silica was observed to fall off the strips. In this example, the silica weight loss was equivalent to about 1.7% of the total weight of the strips, which was equivalent to about 8% of the weight of the added silica.
[0389] *****
[0390] Although various aspects are described in detail in the context of preferred embodiments, it is easy for a person skilled in the art to discern the systems, processes, performances and methods to be protected from the description herein. Many embodiments and adjustments (except the systems and processes described herein) in the systems and processes protected by the present invention and the claims, as well as other changes, modifications and equivalent arrangements and methods, can be easily obtained or reasonably suggested from the present invention and its foregoing description, and such situations are within the scope of substantial protection or claims. In addition, any sequence of steps and / or time sequence of various process flows described and claimed herein are considered to be the best mode for implementing the claimed systems and process flows. It should also be understood that although the steps of various process flows can be shown and described as being performed in a preferred order or time sequence, the steps of any such process flow are not limited to any particular order or sequence, and there is no specific description to limit the specific order of such steps to achieve a specific expected result. In general, the steps of these processes can be performed in various different orders and sequences, and such orders and sequences are still within the scope of application of the claimed systems and process flows. In addition, some steps can be performed simultaneously and synchronously with other steps.
[0391] The embodiments are selected and described to illustrate the principles of the claimed systems and processes and their practical applications so that other technicians in the industry can make full use of these systems, processes and various embodiments and make appropriate modifications for the desired specific use. Alternative embodiments will become apparent to those skilled in the art without departing from the principles and scope of application. Therefore, the scope of application of the claimed systems and processes is defined by the appended claims rather than the foregoing description and the exemplary embodiments described therein.
Claims
1. A natural rubber composition comprising natural rubber, an aminoalkyl silsesquioxane polymer and a stabilizer, wherein: The aminoalkyl silsesquioxane polymer is formed by a chemical reaction of an aminoalkyl silsesquioxane oligomer having three, four, five, six or seven silicon atoms, wherein the formed aminoalkyl silsesquioxane polymer has a continuous molecular silica network formed in situ, and wherein the stabilizer is selected from the group consisting of glucono delta-lactone and gluconic acid. 2 . The natural rubber composition of claim 1 , wherein the aminoalkyl silsesquioxane oligomer comprises an aminoalkyl silsesquioxane-alkyl silsesquioxane copolymer oligomer. 3 . The natural rubber composition of claim 1 , wherein the aminoalkyl silsesquioxane oligomer comprises an aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer.
4. The natural rubber composition of claim 3, wherein the aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to vinyl silsesquioxane repeating units in the range of 3:2 to 6:
1. 5 . The natural rubber composition of claim 1 , wherein the aminoalkyl silsesquioxane oligomer has an average molecular weight in the range of 330 to 552. 6 . The natural rubber composition of claim 1 , wherein the aminoalkyl silsesquioxane oligomer comprises an aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer. 7 . The natural rubber composition of claim 6 , wherein the aminopropylsilsesquioxane-methylsilsesquioxane copolymer oligomer comprises 3 to 5 aminopropyl groups and 1 to 2 methylpropyl groups.
8. The natural rubber composition of claim 6, wherein the aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer has a ratio of aminopropyl silsesquioxane repeating units to methyl silsesquioxane repeating units in the range of 3:2 to 6:
1.
9. The natural rubber composition of claim 1, wherein the aminoalkyl silsesquioxane oligomer comprises an aminoalkyl silsesquioxane homopolymer oligomer.
10. The natural rubber composition of claim 9, wherein the alkyl group of the aminoalkylsilsesquioxane homo-oligomer contains one, two, three, four, five or six carbon atoms.
11. A natural rubber composition comprising natural rubber, an aminoalkyl silsesquioxane polymer and a stabilizer, wherein: The aminoalkyl silsesquioxane polymer is formed from an aqueous solution containing aminoalkyl silsesquioxane oligomers, wherein the formed aminoalkyl silsesquioxane polymer has a continuous molecular silica network formed in situ, and wherein the stabilizer is selected from the group consisting of glucono delta-lactone and gluconic acid.
12. A method of forming a natural rubber composition comprising the steps of: mixing natural rubber latex with a silsesquioxane oligomer solution, wherein the silsesquioxane oligomer is an aminoalkyl silsesquioxane oligomer; and The resulting mixture is dried, wherein, before mixing the silsesquioxane oligomer solution with the natural rubber latex, a stabilizer is mixed with the silsesquioxane oligomer solution, wherein the stabilizer is selected from the group consisting of glucono delta-lactone and gluconic acid, and The solution of aminoalkyl silsesquioxane oligomer forms an aminoalkyl silsesquioxane polymer having a continuous molecular silica network formed in situ.
13. The method of claim 12, wherein the silsesquioxane oligomer is water soluble.
14. The method of claim 12, further comprising the steps of: Precipitated silica is added to the silsesquioxane oligomer solution before mixing the silsesquioxane oligomer solution with the natural rubber latex.
15. The method of claim 12, wherein the aminoalkyl silsesquioxane oligomer is selected from the group consisting of aminopropyl silsesquioxane-vinyl silsesquioxane copolymer oligomer and aminopropyl silsesquioxane-methyl silsesquioxane copolymer oligomer.
16. A rubber processing additive for preparing a natural rubber composition as claimed in any one of claims 1 to 10, comprising an aqueous solution of aminoalkyl silsesquioxane oligomer and a stabilizer, wherein: The aqueous solution of aminoalkyl silsesquioxane oligomer forms an aminoalkyl silsesquioxane polymer having a continuous molecular silica network formed in situ, and wherein the stabilizer is selected from the group consisting of glucono delta-lactone and gluconic acid.
Citation Information
Patent Citations
Rubber compound containing a polyhedral oligomeric silsesquioxanes
US20030050408A1
Amino Alkoxy-Modified Silsesquioxane Adhesives For Improved Metal Adhesion And Metal Adhesion Retention To Cured Rubber
US20120077922A1